Incidental catheterization of a radical arterial branch during vascular cannulation: A case report. - Konstantinou, Evangelos A; Fotis, Theofanis; Mitsos, Aristotelis; Nomikou, Ioanna; Mamoura, Konstantina; Karavasopoulou, Athina; Bastaki, Maria; Mariolis-Sapsakos, Theodoros; Zarmakoupis, Konstantinos (J Vasc Nurs, 2009)
This articles presents a rare case of accidental insertion of an intravascular catheter into an artery by an experienced nurse (RN). Due to the patient's hypotension, this faulty positioning was misdiagnosed and a potential peripheral ischemic necrosis was, fortunately, avoided only because the anesthesia drug injection was performed through another vein. Clinical signs were also present but were also underestimated. After intra-arterial confirmation of the incorrect position, the catheter was subsequently removed. No further complications were observed.
Keywords: Brachial Artery; Catheterization, Peripheral; Humans; Intraoperative Care; Male; Medical Errors; Middle Aged; Ultrasonography, Doppler